Galectin-3 (MAC-2) controls phagocytosis and macropinocytosis through intracellular and extracellular mechanisms - Rotshenker, Shlomo (Frontiers in Cellular Neuroscience, 2022)
Galectin-3 (Gal-3; formally named MAC-2) is a β-galactoside-binding lectin. Various cell types produce Gal-3 under either normal conditions and/or pathological conditions. Gal-3 can be present in cells’ nuclei and cytoplasm, secreted from producing cells, and associated with cells’ plasma membranes. This review focuses on how Gal-3 controls phagocytosis and macropinocytosis. Intracellular and extracellular Gal-3 promotes the phagocytosis of phagocytic targets/cargo (e.g. tissue debris and apoptotic cells) in “professional phagocytes” (e.g. microglia and macrophages) and “non-professional phagocytes” (e.g. Schwann cells and astrocytes). Intracellularly, Gal-3 promotes phagocytosis by controlling “eat me” signaling pathways that phagocytic receptors generate, directing the cytoskeleton to produce the mechanical forces that drive the structural changes on which phagocytosis depends, protrusion and then retraction of filopodia and lamellipodia as they, respectively, engulf and then internalize phagocytic targets. Extracellularly, Gal-3 promotes phagocytosis by functioning as an opsonin, linking phagocytic targets to phagocytic receptors, activating them to generate the “eat me” signaling pathways. Macropinocytosis is a non-selective endocytic mechanism that various cells use to internalize bulk of extracellular fluid and included materials/cargo (e.g. dissolved nutrients, proteins and pathogens). Extracellular and intracellular Gal-3 control macropinocytosis in some types of cancer. Phagocytosed and macropinocytosed targets/cargo that reach lysosomes for degradation may rupture lysosomal membranes. Damaged lysosomal membranes undergo either repair or removal by selective autophagy (i.e. lysophagy) that intracellular Gal-3 controls.